Organic-mineral coupling in Bohai Bay sediments: A source-sorting-preservation framework - Wenxin Zhou; Jun Sun; Liuling Cheng (Marine Geology, 2026)

Weathering-driven clay mineral evolution regulates altitudinal shifts in carbon stabilization within seasonally frozen soils - Zerun Shen; Lulu Zhao; Han Yang; Anbei Deng; Fuxing Liu; Liuling Cheng; Fuwen Jia; Liao Yang; Genming Luo; Zhong-Qiang Chen; Shucheng Xie (Geochimica et Cosmochimica Acta, 2026)

Centennial environmental evolution and human activity impacts recorded by sedimentary diatoms in the Pearl River estuary - Yaqi Zhao; Yuanliang Zhao; Xiangwei Zhao; Sujata Nilajkar; Liuling Cheng; Wenxin Zhou; You Le; Yang Lu; Jun Sun (Marine Environmental Research, 2026)

The response of diatoms in sediment cores to environmental changes in the Changjiang River estuary over the past century - Yuanliang Zhao; Yaqi Zhao; Sujata Nilajkar; Liuling Cheng; Wenxin Zhou; You Le; Yang Lu; Yi Yang; Jun Sun (Marine Environmental Research, 2026)

Littered cigarette butts in both coastal and inland cities of China: occurrence and environmental risk assessment - Qiying Yang; Weibin Zhong; Yaqian Jiao; Yuan Zhang; Liuling Cheng; Yifan Ruan; Shanshan Yang (Frontiers in Marine Science, 2024)
Cigarette butts (CBs) pollution is a critical global environmental issue, yet limited research exists on CBs pollution in both coastal and inland Chinese cities with varying development levels. This study investigated CBs occurrence, contamination, Cigarette Butts Pollution Index (CBPI), and heavy metal leakage in four cities. The results of CBs collected over multiple days revealed higher contamination levels in coastal city of Dalian (0.10 ± 0.03 CBs/m 2 ), inland cities of Baoding (0.06 ± 0.02 CBs/m 2 ) and Meizhou (0.07 ± 0.02 CBs/m 2 ) compared to first-tier coastal city of Guangzhou (0.03 ± 0.02 CBs/m 2 ). Patterns of CBs occurrence and CBPI varied across land usage and cities development level. SEM and EDS analysis identified microplastics and heavy metal particles released from CBs in water environments. ICP-MS detected a total of 629.7 μg/L of 14 heavy metals. Approximately 1.9 ± 0.9 g/km 2 of heavy metals are leaked daily in Chinese cities due to CBs, posing a severe threat to soil and water safety given the indiscriminate disposal of CBs. This study offers scientific insights into CBs pollution and underscores the pressing need for effective measures to mitigate environmental hazards, particularly heavy metal and microplastics contamination released from CBs in China.